Being Toward 2048: The Future Troubles of Dasein and Why Existential Phenomenological Psychotherapy Will Be Important: Parts I and II (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
What forces might bring new pressures on the individual as the user of therapy and the therapist as the provider, over the next thirty years? Artificial Intelligence, Big Data and advancing medical science are shaping new ways to think about the ontology of Dasein. Using the technique of scenario planning, three visions of future worlds of therapy are presented.
Keywords: Enframing; transindividuation; post-humanism; AI; big data; being-in-the-world; Caring